Study on the correlation between carotid plaque calcification types and acute ischemic stroke - Chu, Tianyu; Guo, Zhongping; Zhang, Yonggang; Liu, Ying; Gu, Yan (Frontiers in Neurology, 2025)
IntroductionComputed tomography angiography (CTA) was used to explore the correlation between the calcification types of carotid plaques and ipsilateral acute ischemic stroke. This could provide new insights into the clinical evaluation and treatment of ischemic stroke.MethodsThis study obtained information on patients undergoing head and neck CTA examinations at the First People's Hospital of Lianyungang between September 2022 and August 2023 to investigate the clinical differences in baseline data between the acute ischemic stroke and control groups. Patients meeting the inclusion and exclusion criteria were classified into 1 to 6 groups according to their plaque calcification characteristics. The correlation between calcified plaque type and ipsilateral acute ischemic anterior circulation stroke was analyzed using paired sample chi-square and Spearman correlation tests.ResultsBased on the inclusion and exclusion criteria, this study included 589 patients with plaques at the bifurcation of the carotid arteries. In both the acute ischemic stroke and control groups, sex, smoking, alcohol consumption, systolic blood pressure, blood sugar, cholesterol, high-density lipoprotein, and homocysteine levels were statistically significant (p < 0.05). During the Spearman correlation analysis between calcification type and acute stroke (1,178 carotid arteries), different calcification types of plaques were linked with ipsilateral acute anterior circulation stroke with statistically significant differences (p < 0.001). Finally, the chi-squared test of the paired samples showed that the grade of plaque calcification is often higher on the side of acute infarction than on the side without acute infarction, and the difference is statistically significant (p < 0.001).DiscussionCarotid plaque calcification is associated with acute ischemic stroke. Our findings provide novel insights into the study of calcification in carotid atherosclerotic plaques and additional radiological evidence to clinically assess the risk of ischemic stroke.